2021
DOI: 10.1590/2175-8239-jbn-2020-0156
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral renal infarction in a patient with severe COVID-19 infection

Abstract: Thromboembolic events are frequent in patients with COVID-19 infection, and no cases of bilateral renal infarctions have been reported. We present the case of a 41-year-old female patient with diabetes mellitus and obesity who attended the emergency department for low back pain, respiratory failure associated with COVID-19 pneumonia, diabetic ketoacidosis, and shock. The patient had acute kidney injury and required hemodialysis. Contrast abdominal tomography showed bilateral renal infarction and anticoagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , 63 , 70 , 73 ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the included studies, 11 reported DKA and COVID-19 in children [ 8 , 11 , 22 , 30 , 34 , 44 , 45 , 56 , 61 , 66 , 72 ], 56 reported DKA and COVID-19 in adults [ 9 , 10 , 12 21 , 23 , 25 29 , 31 33 , 35 43 , 46 55 , 57 – 60 , 62 65 , 67 71 , 73 75 ], and only 1 study reported DKA and COVID-19 in both children and adults [ 24 ]. There were 54 case report [ 8 12 , 14 , 16 , 17 , 19 23 , 25 27 , 29 42 , 44 51 , 53 58 , 60 , 61 , 64 , 66 , 67 , 69 , 71 , 72 , 74 , 75 ], 10 case series [ 13 , 15 , 28 , 43 , 58 , 59 , 62 , 63 , 70 , 73 ...…”
Section: Resultsmentioning
confidence: 99%
“…The median or mean patient age ranged from < 1 years to 66 years across studies. There was an increased male predominance in DKA patients diagnosed with SARS-CoV-2 in most of the studies [n = 373, 58.4%] [ 9 13 , 15 17 , 19 , 20 , 23 , 25 , 26 , 31 33 , 36 , 37 , 39 , 45 , 47 , 50 52 , 55 58 , 60 64 , 67 69 , 74 , 75 ] and majority of the patients belonged to Hispanic (n = 156, 24.4%) and black (n = 98, 15.3%) ethnicity [ 14 16 , 18 , 19 , 21 , 24 , 27 , 28 , 44 46 , 54 , 57 , 58 , 62 , 63 , 65 , 68 , 75 ]. The median BMI for all included patients was 27.3 kg/m 2 [interquartile range (IQR) 24.8–30.6 kg/m 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the cause of renal infarction could not be identified in around 30% of the reported cases. 12 Most patients with renal infarction present with abdominal or flank pain; thus, renal infarction may be misdiagnosed initially as acute renal colic or acute pyelonephritis. 1 In a retrospective study of 14 patients, renal infarction was initially misdiagnosed as renal colic.…”
Section: Discussionmentioning
confidence: 99%
“…Renal infarction was also reported on rare occasions in association with other disorders, including but not limited to aortic dissection, vasculitis, systemic lupus erythematosus (SLE), septic emboli due to infective endocarditis, sickle cell diseases, and renal arteries fibromuscular dysplasia (FMD). Nevertheless, the cause of renal infarction could not be identified in around 30% of the reported cases 12 . Most patients with renal infarction present with abdominal or flank pain; thus, renal infarction may be misdiagnosed initially as acute renal colic or acute pyelonephritis 1 .…”
Section: Discussionmentioning
confidence: 99%